2021
DOI: 10.1210/clinem/dgab496
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Cardiac Lipid Sensing Triggers an Early and Sex-related Metabolic Energy Switch in Intrauterine Growth Restriction

Abstract: CONTEXT Intrauterine growth restriction (IUGR) is an immediate outcome of an adverse womb environment, exposing newborns to developing cardiometabolic disorders later in life. This study investigates the cardiac metabolic consequences and underlying mechanism of energy expenditure in developing fetuses under conditions of IUGR. METHODS Using an animal model of IUGR characterized by uteroplacental vascular insufficiency, mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 93 publications
0
10
1
Order By: Relevance
“…We also note sex specific modulation in pathways associated with mitochondrial function in day 90 fetal LV only in females with prenatal T excess. Sex specific metabolic reprogramming has been noted in a rodent model of IUGR with late gestation female fetuses manifesting upregulation in genes associated with mitochondrial function 51 . Although low birth weight is also a characteristic of prenatal T-treated female sheep 52 , in contrast to the aforementioned study, pathways associated with mitochondrial function were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…We also note sex specific modulation in pathways associated with mitochondrial function in day 90 fetal LV only in females with prenatal T excess. Sex specific metabolic reprogramming has been noted in a rodent model of IUGR with late gestation female fetuses manifesting upregulation in genes associated with mitochondrial function 51 . Although low birth weight is also a characteristic of prenatal T-treated female sheep 52 , in contrast to the aforementioned study, pathways associated with mitochondrial function were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…It results in perinatal cardiomyocyte injuries, inflammation in microglial cells, and metabolic alteration of skeletal muscle (27). Notably, to date, most studies have focused on the short-term perinatal damage due to IUGR (18,27). In clinical research, IUGR has been linked with a long-term risk of cardiovascular complications (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that IUGR can cause cardiac and skeletal muscle dysfunction of metabolism during the perinatal period and early life (16,17). In a recent study, Maréchal et al (18) detected an alteration in lipid metabolic gene reprogramming and changes in long-chain fatty acid profile with increased oxidative stress in cardiac muscle samples from IUGR rats at birth, which provided an essential molecular basis secondary to IUGR. Notably, however, whether such metabolic alteration remains long-term is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that fetal weight was strongly associated with impaired tolerance to severe hypoxia in preterm fetal sheep, particularly in males, and that the pattern of impaired failure of tolerance to hypoxia was sex dependent (Bennet et al, 2007). Others report that FGR reduces cardiac myocyte endowment in a sex-specific manner (Botting et al, 2018) and alters cardiac energy management (Maréchal et al, 2021).…”
Section: Insights From Animal Modelsmentioning
confidence: 97%
“…Critically, pre-clinical studies in a variety of species demonstrate that FGR is also associated with effects on other organs such as the kidney, with reduced nephron endowment and associated reduced filtration capacity (Mitchell et al, 2004), and heart, with reduced cardiac myocyte endowment, impaired maturation, remodeling of cardiac vasculature and a switch in energy substrate use (Louey et al, 2007;Wang et al, 2013;Botting et al, 2018;Masoumy et al, 2018;Maréchal et al, 2021;Drake et al, 2022). Altered renal and cardiac development are strongly linked with later-life risks for cardiovascular disease (Masoumy et al, 2018;Fung and Zinkhan, 2021).…”
Section: Insights From Animal Modelsmentioning
confidence: 99%